SAT0258 Weekly split dose compared with single dose oral methotrexate reduced polyglutamylation in red blood cells and increased the risk of adverse events in patients with rheumatoid arthritis. (12th June 2018) - Yoshioka, Y.; Katayama, K.; Kasama, T.; Sato, M.; Ohno, S.; Amasaki, Y.; Kataoka, H.; Kanai, D.; Suda, A.; Okamoto, M.; Sasano, M.; Nagaoka, S.; et al.
Abstract : Background: Methotrexate (MTX) is a well-known anchor drug for rheumatoid arthritis (RA); however, dose regimens vary. We previously reported in EULAR2015 that split dose weekly oral methotrexate induced elevation of AST and ALT in association with elevation of MTX with 2 glutamates (MTX-PG2) in a single-centre trial. Objectives: We performed a multi-centre randomised controlled trial to compare the incidence of adverse events using single and split dose regimens. Methods: Six hospitals and 2 rheumatology clinics participated in this study. Seventy-eight patients with insufficient control on MTX 8 mg/week were randomly assigned to 2 groups, i.e., a single weekly dose regimen with 39 patients and a 3 dose per week regimen with 39 patients. The MTX dose in all patients was gradually increased to 16 mg/week. The primary endpoint was the occurrence of liver dysfunction during the observation period (20 weeks). Other endpoints included the incidence of adverse events and the changes from baseline in the disease activity score (DAS28) based on ESR or CRP, the Simplified Disease Activity Index (SDAI), and MTX-PG at week 20. Results: There were no differences between the groups in baseline data and MTX dose at 20 weeks (single dose: 10.2±0.8 vs. 3-dose: 10.2±0.9 mg/week). Liver dysfunction occurred in 3 patients (7.7%) receiving the single dose regimen and in 5 patients (13.2%) receiving the 3-dose regimen, but there was no significant difference in the incidence in both groups (p=0.455). There was a significant difference in the incidence of adverse events (gastrointestinal disorder was most common) between single dose (11 patients, 28.9%) and 3-dose (20 patients, 52.6%) regimens (p=0.036). There was no significant difference in the changes from baseline in DAS28-ESR (−1.55 vs. −1.36), DAS28-CRP (−1.31 vs. −1.26), or SDAI (−9.45 vs. −10.11). Compared to the single dose regimen, MTX-PG2 was significantly increased in the 3-dose regimen, and MTX-PG3, -PG4, and -PG5 were significantly increased in the single dose regimen (table 1). Conclusions: There were no differences in the incidence of liver dysfunction and efficacy according to the oral MTX dose regimen; however, split weekly dosing compared with single weekly dosing reduced polyglutamylation and increased the risk of adverse events. Acknowledgements: Clinical registration: UMIN000021157 Disclosure of Interest: Y. Yoshioka: None declared, K. Katayama: None declared, T. Kasama: None declared, M. Sato: None declared, S. Ohno: None declared, Y. Amasaki: None declared, H. Kataoka: None declared, D. Kanai: None declared, A. Suda: None declared, M. Okamoto Employee of: AYUMI Pharmaceutical Corporation, M. Sasano: None declared, S. Nagaoka: None declared, A. Sagawa: None declared